A Study on Green Hydrogen Production Using PV and Grid with Renewable Energy Certificate in Tambak Lorok Combined Cycle Power Plant - Nurachman, Rizky Andri; Fauzi Soelaiman, Tubagus Ahmad (ITB Graduate School Conference, 2025)
This study assesses the feasibility of green hydrogen production at the Tambak Lorok Combined Cycle Gas Turbine (CCGT) complex through the integration of a photovoltaic (PV) system and grid electricity with Renewable Energy Certificate (REC). PVsyst was used for energy modeling, while techno-economic simulation was conducted in HOMER Pro. The analysis focuses on full-load operational scenarios and evaluates key indicators such as the Levelized Cost of Electricity (LCOE) and the Levelized Cost of Hydrogen (LCOH). Results show that Scenario 1, which utilizes captive power, achieves the most favorable outcome with an LCOE of 1,887.8 IDR/kWh and an LCOH of 140,884 IDR/kg, producing 10.6 tons of excess hydrogen annually. These values are competitive compared to other hydrogen production facilities. In contrast, Scenario 2, which relies on grid electricity, requires cost optimization to become as competitive as Scenario 1, while also meeting green certification standards such as CertifHy, I-REC, and RE100. The findings provide a valuable reference for power plants aiming to adopt similar PV and grid-based configurations for green hydrogen production.